2022
DOI: 10.1136/gutjnl-2021-325080
|View full text |Cite
|
Sign up to set email alerts
|

EUS versus MRCP to perform ERCP in patients with intermediate likelihood of choledocholithiasis: a randomised controlled trial

Abstract: ObjectiveIn patients with an intermediate likelihood of choledocholithiasis, European Society of Gastrointestinal Endoscopy (ESGE) guidelines recommend endoscopic ultrasound (EUS) or magnetic resonance cholangiopancreatography (MRCP) to diagnose choledocholithiasis to make the indication for endoscopic retrograde cholangiopancreatography (ERCP) treatment; there is no randomised control trial to compare both in this setting.DesignPatients with suspected choledocholithiasis satisfying ESGE guideline’s intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Many other studies that evaluated the diagnosis of choledocholithiasis by EUS showed variable results regarding sensitivities and specificities. For example, Jagtap et al [ 13 ] showed that the sensitivities of both EUS and MRCP were similarly high (92%-98%). Also, Patel et al [ 11 ] showed that the sensitivity and specificity of EUS were 93% and 97.3%, respectively, but most included patients had a high probability of choledocholithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies that evaluated the diagnosis of choledocholithiasis by EUS showed variable results regarding sensitivities and specificities. For example, Jagtap et al [ 13 ] showed that the sensitivities of both EUS and MRCP were similarly high (92%-98%). Also, Patel et al [ 11 ] showed that the sensitivity and specificity of EUS were 93% and 97.3%, respectively, but most included patients had a high probability of choledocholithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…23 Nitin et al stated that sensitivity of ERCP and MRCP is 90% and 80% respectively in the detection of choledocholithiasis. 24 Recently a study conducted in USA by David et al reported that in the cases of choledocholithiasis abnormally dilatation of CBD causes reduced sensitivity of MRCP, so ERCP is suitable in such cases. 25 However previous literature states usefulness of MRCP with minimum complications and higher diagnostic accuracy in biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The choice between MRCP or EUS is driven by local availability of resources or expertise and preference of healthcare professional or patient as EUS and MRCP have comparable sensitivity and specificity. 11 However, usage of IOC during cholecystectomy might be more cost-effective for intermediate likelihood group compared with EUS/MRCP followed by ERCP and subsequent cholecystectomy or it can be substratified to reduce need for EUS or MRCP. 12 13…”
Section: Discussionmentioning
confidence: 99%